POTENSI BEBERAPA TANAMAN ATRAKTAN DALAM PENGENDALIAN KEONG MAS (Pomacea canaliculata L.) PADA TANAMAN PADI SAWAH DI DESA GOLO BORE, KECAMATAN NDOSO, KABUPATEN MANGGARAI BARAT - Nurung, Gaudensius Vidianto; Harini, Titik Sri; Ludji, , Rika; Nanotek, Petronella S. (JURNAL AGRISA, 2024)
This research was carried out in Golo Bore Village, Ndoso District, West Manggarai Regency. From June to July 2023. This research aims to determine the potential of several types of plants that function as attractants for golden snails in paddy fields in Golo Bore Village, Ndoso District, Manggarai Regency. West This research used a Completely Randomized Design method with four treatments and four replications at the research location in Golo Bore Village, Ndoso District, West Manggarai Regency which has rice fields that are entering the vegetative phase. The results of sagam testing show that attractant plant types have a significant influence very real in the golden snail population. The highest average population of golden snails was found in the taro leaf treatment, namely 33 individuals, followed respectively by papaya leaves, 27 individuals, banana leaves (20 individuals) and the lowest population of golden snails was found in the cassava leaf treatment, namely 16 individuals.